Real-time power quality monitoring system based on TMS320CV5416 DSP processor - Abdullah, Abdul Rahim; Sha`ameri, Ahmad Zuri (2005)
Any disturbance in the power-line can cause disruption in manufacturing process or services provided. Under worst case conditions results in equipment failure and subsequent increase in cost of operation. Monitoring and analysis of power-line waveforms are essential to provide assessment of the power quality. This project presents a system that can monitor power-line voltage and current waveforms. Signal analysis techniques such as the periodogram and spectogram are employed to analyze power-line voltage and current variations. The heart of the system is the Texas Instruments DSP (Digital Signal Processing) TMS320CV5416 and user interface on a personal computer was developed using the Visual Basic version 6.0 to display power line measurement parameters.